Nouvelles données sur le Miocène moyen marin ("Sallomacien") de Gironde (Bassin d'Aquitaine-France) Approche des paléoenvironnements New data about the maine Middle Miocene ("Sallomacian") of Gironde (Aquitaine Basin); paleoecological outline - Follioti, M. (1992)
The Mid Miocene marine formations of Salles area (former "Sallomacian" stage) have been studied again from numerous outcrops and cores. The deep structural framework influences notably of the characteristics and distribution of the deposits, which are neritic. The stratigraphy is stated precisely thanks to the planktonic fauna and floradetailed examination (probably Serravallian zones NN6 - N12). Several paleobiofacies are reconstituted from the rich invertebrate faunas, which give also paleoclimatic data.